Cohort study of mesenteric panniculitis and its relationship to malignancy. Issue 12 (12th August 2016) - Buchwald, P; Diesing, L; Dixon, L; Wakeman, C; Eglinton, T; Dobbs, B; Frizelle, F
Abstract: Background: Mesenteric panniculitis (MP) is a rare condition that historically has been associated with the presence of malignancy. Paraneoplastic phenomena in general regress with cure and in most cases with treatment of the cancer. This study was undertaken to determine whether MP regressed with cancer treatment and cure. Methods: This was a retrospective review of a database of all patients with MP confirmed on CT between 2003 and August 2015 at Christchurch Hospital. Patients were categorized as having malignant or non-malignant disease, and follow-up scans were assessed for remission of MP. Patients with malignancy were further categorized as having malignancy cured or not cured. Results: A total of 308 patients were identified with possible MP; 135 were excluded as radiological appearances were not typical of MP (43 patients) or there was no follow-up CT (92). Of 173 patients (131 men) included, 75 (43·4 per cent) were diagnosed with malignancy. Follow-up imaging showed that 33 patients (19·1 per cent) had remission of MP, whereas 140 (80·9 per cent) had no remission. There was no difference in the rates of MP remission in the malignancy versus no malignancy groups ( P = 1·000), or between groups in which malignancy was cured or not cured ( P = 0·572). Nor was there any difference in the rates of MP remission in malignancy cured versus no malignancy groups ( P = 0·524). Conclusion: MP does not behave like a paraneoplastic phenomenon. The association with malignancy is most likely an epiphenomenon of the many CT images acquired for staging of cancer. Abstract : Definitive perspective on the subject